2017
DOI: 10.1007/s00216-017-0491-7
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-based fluorescence-quenching lateral flow strip for rapid detection of mercury (II) ion in water samples

Abstract: Divalent mercury ion (Hg) is one of the most common and stable forms of mercury pollution. In this study, a skillfully designed lateral flow strip (LFS) was developed for sensitive detection of Hg in river water samples. Aptamer, a specific oligonucleotide probe, was used to selectively identify and target Hg instead of antibody in traditional immunechromatographic strips; and the fluorescence-quenching system was used to generate positive and low background florescence signals in the competitive-likely LFS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…17 It has been extensively applied for the determination of heavy metal ions, such as copper, lead, cadmium and mercury. 18,19 The designed uorescent probes are mainly based on rhodamine, 20 boron-dipyrromethene, 21 thymine, 22 noble metal nanoparticles, 23 and quantum dots. 24 Chen et al proposed novel Hg 2+ sensors using tetraphenylethene derivatives as donors and a rhodamine core as the acceptor with high energy transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…17 It has been extensively applied for the determination of heavy metal ions, such as copper, lead, cadmium and mercury. 18,19 The designed uorescent probes are mainly based on rhodamine, 20 boron-dipyrromethene, 21 thymine, 22 noble metal nanoparticles, 23 and quantum dots. 24 Chen et al proposed novel Hg 2+ sensors using tetraphenylethene derivatives as donors and a rhodamine core as the acceptor with high energy transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The measured signal intensity matched with the machine's image (Figure A and B). The ratio of intensity in test line ( I T ) to intensity in control line ( I C ) ( I T / I C ) was used to replace intensity of T‐line to avoid sample disturbance, humidity, and photographing, and so forth, which might have some effect on the signal of T‐line . The reaction intensity ratio histograms of SAS‐LFIA and cLFIA suggested that the I T / I C values of SAS‐LFIA were much higher than those of cLFIA (Figure C), and had good repeatability.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this type of aptasensor is more suitable for real-time detection [ 38 ]. The highly flexible structure of aptamers is suitable for construction of different types of fluorescent sensing devices, including molecular beacons, duplex structure with complementary sequences, structure switching, and competitive laser-based lateral flow assays [ 39 , 40 , 41 , 42 ]. An increasing number of fluorescence-base aptasensors has been used for monitoring low molecular weight pollutants in water sources, such as graphene oxide (GO)-based fluorescence resonance energy transfer (FRET) assay [ 43 ], magnetic bead composites coated with gold nanoparticles (AuNPs) and nicking enzyme fluorescence assay [ 44 ], carbon nanotubes (CNTs)-based fluorescent assay [ 45 , 46 ], biocompatible graphene quantum dots (QDs)-based fluorescent nanosensor [ 47 ].…”
Section: Aptasensors and Their Applications For Detecting Low Molementioning
confidence: 99%
“…Currently, many types of aptasensors were developed for detecting the Hg 2+ in water samples based on the different platforms, including electrochemistry, colorimetric and fluorescence-based analysis [ 73 , 74 , 75 ]. In addition, many signal amplification modes or novel platforms such as chemiluminescence (CL) [ 73 ], electrically rGO-based chemiresistor [ 69 ], silicon nanomaterials (SiNPs)-based fluorescence [ 70 ], fluorescence lateral flow strip [ 40 ] and exothermic chip [ 71 ] have also been developed for detecting the Hg 2+ in water samples. Among those, a simple and rapid CL aptasensor for Hg 2+ was developed in natural water samples with a limit of detection (LOD) of 16 pM within 30 min.…”
Section: Aptasensors and Their Applications For Detecting Low Molementioning
confidence: 99%